CORPORATE GOVERNANCE GUIDELINES AND SIGNIFICANT CORPORATE ACTIVITIES OF STATE-OWNED ENTERPRISES: OPTIMISING RESTRUCTURING, STATE CAPITAL INCREASES, AND BUSINESS DEVELOPMENT AS PILLARS OF SUSTAINABILITY AND COMPETITIVENESS IN THE GLOBAL ECONOMY ERA - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
This study analyses the role of SOE governance guidelines in optimising significant corporate activities, namely restructuring, state capital injections (PMN), and business development, as key pillars of sustainability and competitiveness in the global economy. Through a descriptive-comparative literature review approach, the study explores two main discussions: the optimisation of governance in restructuring and PMN for structural efficiency and fiscal accountability, and ESG-based business development for innovation and global expansion. The results show that holistic governance guidelines—integrating transparency, accountability, and continuous evaluation—can overcome the challenges of political intervention and capability gaps, thereby improving the financial performance of SOEs and their contribution to national development. Recommendations include reforming digital governance regulations and strengthening the independence of the board of commissioners to realise the vision of Indonesia Emas 2045.